(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The article considers proposals for teaching children and adolescents theater arts in schools through virtual meetings, due to the impossibility of having on-site classes brought by the pandemic. It highlights interesting solutions devised by teachers in the field of acting games and performances. However, structural educational problems, as well as material difficulties that meet particularly the lower income classes, set up strong obstacles to the effectiveness of that practice.